A 1-year randomized controlled study of everolimus versus mycophenolate mofetil with reduced-dose cyclosporine in maintenance heart transplant recipients - Bara, Christoph Leon; Dengler, Thomas; Hack, M. A.; Ladenburger, S.; Lehmkuhl, Hans Brendan (Transplantation proceedings, 2013)
Background - The aim of this study was to demonstrate noninferiority of everolimus with reduced cyclosporine (CsA) vs mycophenolate mofetil (MMF) with reduced CsA in improving renal function. - Methods - In this 1-year randomized, open-label, noninferiority study in maintenance heart transplant recipients with impaired renal function 70 patients received everolimus (n = 36) or MMF (n = 34) in combination with reduced CsA. The planned sample size was not reached as the study was prematurely discontinued due to slow recruitment. - Results - Noninferiority of the everolimus regimen could not be shown: In the total population MMF seemed to be favorable on renal function assessed by serum creatinine and filtration rates, but not in the subset of patients who reached the intended reduced CsA level. Incidence rates of rejection episodes were significantly higher under MMF at month 6 (P = .0332). - Conclusions - Overall, the results of this trial using reduced CsA in combination with either everolimus or MMF show that there is evidence to reduce the CsA level when everolimus is given concomitantly and that the benefit of MMF with reduced CsA levels is limited due to insufficient immunosuppression.